The Effect of Profitability, Leverage, and Free Cash Flow on Dividend Policy with Good Corporate Governance as a Moderating Variable - Ni Putu Suriani; Ni Gusti Putu Wirawati (International Journal of Economics Accounting and Management, 2025)
This study aims to analyze the effect of profitability, leverage, and free cash flow on dividend policy, with good corporate governance as a moderating variable. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange, using a sample of 20 companies over a three-year observation period from 2021 to 2023,nresulting in a total of 60 data points selected through purposive sampling. This study employed a quantitative approach using secondary data obtained from the companies’ financial statements during the observation period. Hypothesis testing was carried out using Moderated Regression Analysis (MRA). The results indicate that profitability and leverage have no significant effect on dividend policy, whereas free cash flow has a significant negative effect. Managerial ownership was found to weaken the negative effect of free cash flow on dividend policy, but it did not moderate the influence of profitability and leverage. Institutional ownership did not moderate the effects of profitability, leverage, or free cash flow on dividend policy